Act of others and its effect on provisions of tort liability (Comparative study) (Al-Mansour Journal, 2022)
The foreign cause is one of the factors that negate the causal association, which is one of the pillars of civil liability that it denies One of the forms of the foreign cause is what is known as "the act of others" or "the fault of others" the focus of our research, which did not adequately address the statement of its concept most of the legislation, which prompted the jurisprudence to determine its legal nature in terms of its definition and identification and the features of its achievement shaping it from other foreign cause images, And that's what the first research is about, On the other hand, there are the effects of the act of others that are being undermined by the defendant's position in the civil liability claim if he can prove that the damage achieved was the result of the act of others to be able to dispose of responsibility completely or partially, which is what is addressed in the research in a second research, At the end of the research, we will be briefed on the most fundamental results of the research: that the term "third party" is a vague and non-specific legal term, but its meaning varies according to what it refers to in each case, and the possibility of the defendant to fully deny himself civil responsibility in the case or Partial if it is established that the damage was caused by the intervention of a person or the multiplicity of causes in his rhythm.
Keywords: Others; judgments; liability